ANALISA TINGKAT KEPATUHAN PENGUNGKAPAN WAJIB KONVERGENSI IFRS 2012 : STUDI KASUS PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA 2011-2012 - Kurniawati Kurniawati (Universitas Bunda Mulia, 2017)
A recent trending issue in the world of accounting is the issue of the convergence of the 2012 International Financial Reporting Standards (IFRS). The process of this convergence has started since 2008 and is expected to be finished by 2011, so that it may be fully implemented in 2012. There are several main characteristics of IFRS, i.e. principal based, fair value, and disclosure.This research is conducted with the purpose of assessing the level of compliance with mandatory disclosure IFRS Convergence 2012 for consumer goods companies listed in the Indonesian Stock Exchange within the period of 2011-2012. The sample is selected using purposive sampling techniques and twenty seven (27) research samples are acquired in the consumer goods industry. To measure the level of compliance with mandatory disclosure, the Dichotomous method is used in this research by using items from the IFRS Presentation & Disclosure Checklist issued by Deloitte in 2012.The result of this research shows that the average level of compliance with mandatory disclosure IFRS Convergence 2012 for consumer goods companies is 75.95% which can be seen from four PSAK, i.e. PSAK 14, PSAK 16, PSAK 13 and PSAK 30.The highest level is from PSAK 16, followed by PSAK 14 in second, and PSAK 13 and PSAK 30 in third and fourth respectively. Keyword: International Financial Reporting Standards (IFRS) Convergence, Compliance, Mandatory disclosure level, International Accounting Standards, Consumer goods company